2020
DOI: 10.1097/coc.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on the Use of Photon-based Stereotactic Radiosurgery Versus Fractionated Stereotactic Radiotherapy for the Treatment of Uveal Melanoma

Abstract: Purpose: The purpose of this report is to assess the efficacy and adverse event profile of photon-based stereotactic radiosurgery (SRS) compared with fractionated stereotactic radiotherapy (fSRT) for the treatment of uveal melanoma. Primary outcomes include incidence proportions of local control, enucleation, metastatic progression, disease-specific, and overall mortality. Treatment-related toxicities such as incidence proportions of radiation retinopathy, neovascular glaucoma, optic neuropathy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Thirty-three pyroptosis-related genes were extracted from prior studies in Table S2 19 23 . The expression levels of 33 pyroptosis-related genes were retrieved from the TCGA and GEO datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-three pyroptosis-related genes were extracted from prior studies in Table S2 19 23 . The expression levels of 33 pyroptosis-related genes were retrieved from the TCGA and GEO datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Bensoussan et al studied 492 patients after PBT, reporting an incidence of 27.0% [59]. Kosydar et al conducted a meta-analysis on the use of Photon-based SRT versus fSRT and reported an overall incidence of 16.8% [125]. It is noteworthy that the time frame also varies greatly, with certain patients experiencing early-onset NVG after just a few months, while others develop late-onset NVG several years after treatment.…”
Section: Secondary Glaucoma-neovascular Glaucomamentioning
confidence: 99%
“…Irradiation of the tumor can be performed in a single session with a high dose of photons (SRS) or in a fractionated form (SRT) [ 11 , 20 , 25 , 26 , 27 , 28 ]. The main advantages of these methods include their minimal invasiveness, excellent local tumor control, relatively wide availability and low costs [ 20 , 25 , 26 , 28 , 29 ]. Some researchers have indicated their disadvantages in the form of lower precision and the associated higher number of post-radiation complications, mainly secondary glaucoma and enucleation compared with brachytherapy and proton therapy [ 11 , 20 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have indicated their disadvantages in the form of lower precision and the associated higher number of post-radiation complications, mainly secondary glaucoma and enucleation Stereotactic radiotherapy (SRT) and stereotactic radiosurgery (SRS), which also represent external-source radiotherapy, have gained popularity in the treatment of uveal melanoma in recent years. Irradiation of the tumor can be performed in a single session with a high dose of photons (SRS) or in a fractionated form (SRT) [11,20,[25][26][27][28]. The main advantages of these methods include their minimal invasiveness, excellent local tumor control, relatively wide availability and low costs [20,25,26,28,29].…”
Section: Introductionmentioning
confidence: 99%